2022
DOI: 10.1590/0104-9224/si27.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Heat Input and Cooling Rate of Rail Flash-Butt Welding using Finite Element Method Simulation

Abstract: Simulations using the finite element method (FEM) were done to understand the effects of heating/cooling rates on the distribution of residual stresses. Two material parameters from rails were used while the boundary conditions remained constant: heat-affected zone size, maximum temperature and heating extraction rate. To complement the analysis, a flash-butt weld of a Premium rail was done with welding parameters adjusted to obtain a narrow HAZ, without forced cooling, to examine the microstructure formed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
11

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 27 publications
3
6
0
11
Order By: Relevance
“…According to the AREMA recommendation [18], flash-butt welding is controlled to minimize the amount of martensite in any rail region. Also, the findings of both Skyttebol et al [10] and Pereira et al [16] reveal no major change in the hardness and microstruc-ture of the heat-affected zone (HAZ). Thus, phase transformation is not considered in the present numerical investigation.…”
Section: Governing Equations For Flash-butt Weldingmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the AREMA recommendation [18], flash-butt welding is controlled to minimize the amount of martensite in any rail region. Also, the findings of both Skyttebol et al [10] and Pereira et al [16] reveal no major change in the hardness and microstruc-ture of the heat-affected zone (HAZ). Thus, phase transformation is not considered in the present numerical investigation.…”
Section: Governing Equations For Flash-butt Weldingmentioning
confidence: 95%
“…They found that the rapid quenching before the complete austenitepearlite transformation can increase the tensile residual stress. Pereira et al [16] performed a metallographic examination of a flash-butt weld joint. They found that there was no formation of acicular microstructures (i.e., martensite/bainite) in the web region and the rail foot, which were the regions with a higher cooling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta menor tendência de formar ferrita pró-eutetoide também é observada nos perfis de dureza dos trilhos usados, nos quais não há diminuição evidente da dureza na área central das soldas. A formação de ferrita pró-eutetoide é comum para aços com carbono equivalente mais próximo do equilíbrio eutetoide e tem sido observada por vários autores [31,33,116].…”
Section: Discussionunclassified
“…Uma diferença entre as simulações presentes e as simulações realizadas por Pereira et al [116] é a consideração no presente estudo da simetria de reações na face "aquecida" pelo processo de soldagem de topo por centelhamento (Flash-Butt). O presente modelo considerou simetria de reação entre os eixos x e y (que são os sentidos transversal e vertical do trilho respectivamente), porém deixou-se o eixo z (sentido horizontal ao trilho) livre de restrição ao deslocamento.…”
Section: Metodologiaunclassified